Continuum dislocation dynamics-based grain fragmentation modeling. (March 2019) - Kobaissy, A.H.; Ayoub, G.; Toth, L.S.; Mustapha, S.; Shehadeh, M.
Abstract: This paper proposes a grain fragmentation modeling approach that couples continuum dislocation dynamics analysis with a crystal-plasticity framework. The proposed model investigates the microstructural features of FCC metals subjected to severe plastic deformation (SPD) processes. Several aspects of the deformation process were considered in this model, including texture evolution, statistically stored dislocations (SSDs) and geometrically necessary dislocations (GNDs) densities evolution, and grains fragmentation and its effect on the overall mechanical response. The proposed model was applied to a reference volume element (RVE) in which the grains are distributed and assigned an initial position. Within the model, each grain has the ability to split into 1024 new smaller grains, which subsequently leads to strain hardening and grain refinement. The latter was modeled by accounting for the grain-grain interaction, for which the concept of the GNDs is incorporated into the mean free path of the dislocations. GNDs were assumed to be induced by grain boundaries that restrict the free deformation of a grain and result in an increase of stresses leading to the grain size reduction. Our grain fragmentation hypothesis was based on the Tóth et al. (2010) lattice curvature assumption [Tóth, L.S., Estrin, Y., Lapovok, R., Gu, C., 2010. A model of grain fragmentation based on lattice curvature. Acta Mater. 58, 1782–1794]. The grain refinement procedure was triggered when the misorientation threshold between subgrains was exceeded. The model parameters were calibrated using torsion tests of pure copper material. The simulation results give reliable predictions of the crystallographic texture, the evolution of dislocation density, and the final grain size based on available experimental data. Highlights: The proposed model investigates the microstructural features of FCC metals subjected to severe plastic deformation (SPD). A grain fragmentation modeling approach is proposed that couples continuum dislocation dynamics with crystal-plasticity. The deformation processes considered include; texture evolution, SSDs and GNDs densities evolution, and grains fragmentation.